Promoting transparency in forensic science by integrating categorical and evaluative reporting through decision theory - Sigman, Michael E.; Williams, Mary R. (Frontiers in Analytical Science, 2023)
Forensic science standards often require the analyst to report in categorical terms. Categorical reporting without reference to the strength of the evidence, or the strength threshold that must be met to sustain or justify the decision, obscures the decision-making process, and allows for inconsistency and bias. Standards that promote reporting in probabilistic terms require the analyst to report the strength of the evidence without offering a conclusive interpretation of the evidence. Probabilistic reporting is often based on a likelihood ratio which depends on calibrated probabilities. While probabilistic reporting may be more objective and less open to bias than categorical reporting, the report can be difficult for a lay jury to interpret. These reporting methods may appear disparate, but the relationship between the two is easily understood and visualized by a simple decision theory construct known as the receiver operating characteristic (ROC) curve. Implementing ROC-facilitated reporting through an expanded proficiency testing regime may provide transparency in categorical reporting and potentially obviate some of the lay jury interpretation issues associated with probabilistic reporting.